Low-dose melphalan in elderly patients with relapsed or refractory acute myeloid leukemia: A well-tolerated and effective treatment after hypomethylating-agent failure. (October 2019) - Stratmann, Jan; van Kann, Elisabeth; Rummelt, Christoph; Koschade, Sebastian; Röllig, Christoph; Lübbert, Michael; Schaich, Markus; Parmentier, Stefani; Sebastian, Martin; Chromik, Joerg; Becker von Rose, Aaron; Ballo, Olivier; et al.
Highlights: Oral Melphalan is a safe and effective treatment option in relapsed myeloid leukemia. Patients with prior hypomethylating agent therapy seem to have additional benefit. Melphalan is futile in patients with complex karyotype myeloid leukemia. Abstract: Relapsed or refractory (R/R) disease remains challenging in acute myeloid leukemia (AML), especially in elderly patients not considered eligible for intensive treatment options. We retrospectively evaluated the safety and efficacy of low-dose melphalan (LD-Mel) in a multicenter analysis in patients over 65 years with R/R AML, who previously had received ≥1 non-curative treatment line. The study included 31 patients (median age 77 years) with 1–4 previous treatment lines. Three patients (9.7%) achieved a complete remission. Two patients (6.5%) achieved a partial remission, nine patients (29.0%) had disease stabilization with reduction of peripheral or bone marrow blast burden, resulting in an overall response rate of 16.1% and 45.2% achieved clinical benefit. Responders showed a significantly longer median overall survival than non-responders (16.3 vs. 2.3 months, p < 0.001). Multivariate analysis identified complex karyotype as the only risk factor associated with inferior survival (p < 0.001), whereas prior treatment with hypomethylating agents (HMAs) in 25 of 31 patients was associated with superior OS, regardless of prior response to HMAs (p = 0.03). LD-Mel was well tolerated, with mild myelosuppressive side effects. Conclusively, LD-Mel is an effective treatment option in elderly patients with R/R AML, particularly after HMA therapy and in the absence of a complex karyotype.